Multi-touch human-computer interface - Mi, Qi. (2011)
Nowadays, more and more researches related to human computer interface have been done. Among them, studies on the multi-touch interface come to the fore. Some famous companies released their own touch products. In this project, we studied and implemented a low-cost multi-touch interface. The aim of this interface is to provide a more natural human-computer interaction experience for users.